(untitled) (Altre Modernità, 2014)
The paper is dedicated to the double diaspora of Jews of Cuba and its current literary representation. Cubans of Jewish heritage, have lived on the island of Cuba for centuries. Some Cubans trace Jewish ancestry to Marranos who fled the Spanish Inquisition, though few of these practice Judaism today. There was significant Jewish immigration to Cuba in the first half of the 20th century. Like others, many Jews left Cuba for the United States after the coming of Fidel Castro, and today there is a large community in South Florida. Ruth Behar and Achy Obejas lives in USA since they were children, but they wanted to recreate their double identity - which resembles that of many other cuban Jews in their peculiar american diaspora - the first with the anthropological researche, the second thanks to the novel or the short story.